Entwicklung und Stand der Flurbereinigung in Spanien - Liss, Carl-Christoph (ERDKUNDE, 1985)
In a large part of Spain - namely in its northern provinces, in Galicia, Leon and Old Castile and in the New Castilian provinces of Guadalajara and Cuenca - the traditional agrarian structure is characterized by smallholding and by the fragmentation of holdings and parcels, generally up to a very high and often even to an extreme degree. Notwithstanding this situation and the fact that in Spain there has been, since the end of the 18th century, anintense theoretical discussion about the agrarian problems and also far-reaching political action in other fields of the agrarian structure, there have been - unlike the case in other European countries - no consolidations of holdings up to the middle of this century. Only then, in 1952, did the government launch an extensive land consolidation scheme. Until the end of 1982, 3,846 consolidation operations have been carried through. By means of these operations, 13,174,355 acres of land of 1,708,792 landowners have been redistributed.15,525,450 parcels have been reduced to 2,078,215 new parcels. That means an average reduction of 7.47 to 1.